Multimericity Amplifies the Synergy of BCR and TLR4 for B Cell Activation and Antibody Class Switching - Pone, Egest J.; Hernandez-Davies, Jenny E.; Jan, Sharon; Silzel, Emily; Felgner, Philip L.; Davies, D. Huw (Frontiers in Immunology, 2022)
Sustained signaling through the B cell antigen receptor (BCR) is thought to occur only when antigen(s) crosslink or disperse multiple BCR units, such as by multimeric antigens found on the surfaces of viruses or bacteria. B cell-intrinsic Toll-like receptor (TLR) signaling synergizes with the BCR to induce and shape antibody production, hallmarked by immunoglobulin (Ig) class switch recombination (CSR) of constant heavy chains from IgM/IgD to IgG, IgA or IgE isotypes, and somatic hypermutation (SHM) of variable heavy and light chains. Full B cell differentiation is essential for protective immunity, where class switched high affinity antibodies neutralize present pathogens, memory B cells are held in reserve for future encounters, and activated B cells also serve as semi-professional APCs for T cells. But the rules that fine-tune B cell differentiation remain partially understood, despite their being essential for naturally acquired immunity and for guiding vaccine development. To address this in part, we have developed a cell culture system using splenic B cells from naive mice stimulated with several biotinylated ligands and antibodies crosslinked by streptavidin reagents. In particular, biotinylated lipopolysaccharide (LPS), a Toll-like receptor 4 (TLR4) agonist, and biotinylated anti-IgM were pre-assembled (multimerized) using streptavidin, or immobilized on nanoparticles coated with streptavidin, and used to active B cells in this precisely controlled, high throughput assay. Using B cell proliferation and Ig class switching as metrics for successful B cell activation, we show that the stimuli are both synergistic and dose-dependent. Crucially, the multimerized immunoconjugates are most active over a narrow concentration range. These data suggest that multimericity is an essential requirement for B cell BCR/TLRs ligands, and clarify basic rules for B cell activation. Such studies highlight the importance in determining the choice of single vs multimeric formats of antigen and PAMP agonists during vaccine design and development